Pengaruh Radikal Bebas Terhadap Proses Inflamasi pada Penyakit Paru Obstruktif Kronis (PPOK) - Rivan Virlando Suryadinata (Amerta Nutrition, 2018)
Background: Chronic Obstructive Pulmonary Disease is diseases caused by exposure to cigarette smoke. Cigarette smoke carries free radicals into the airways which can lead to acute exacerbations in patients.Objectives: explanation of inflammatory processes in the airways in patients with PPOK due to an increase in free radicals.Discusion: In the human body, free radicals are metabolic products from normal cells and function as one of the body's defense systems. Free radicals can be Reactive Oxygen Species (ROS) and Reactive Nitrogen Species (RNS), both of which can be obtained from the inside (endogenous) or from outside the body (exogenous). In the pathological, exposure to cigarette smoke causes an imbalance between the amount of free radicals produced in the body so that it can lead to oxidative stress.Conclusion: An increase in the number of free radicals will directly affect inflammatory mediators in the body. Increased free radicals will trigger the inflammatory process locally in the airways and systemically, so increasing the rate of exacerbations in COPD patients.ABSTRAKLatar Belakang : Penyakit PPOK ditimbulkan akibat paparan asap rokok yang terus menerus. Radikal bebas yang dibawa oleh asap rokok terhirup masuk kedalam saluran napas dapat menimbulkan eksaserbasi.Tujuan : Menjelaskan proses eksaserbasi yang dipengaruhi oleh proses inflamasi pada penderita PPOK akibat peningkatan radikal bebas.Ulasan : Pada tubuh manusia, radikal bebas merupakan produk hasil metabolisme dari sel normal. Pada keadaan normal, Radikal bebas berfungsi sebagai salah satu sistem pertahanan tubuh. Radikal bebas dapat berupa Reactive Oxygen Spesies (ROS) dan Reactive Nitrogen Spesies (RNS), keduanya dapat diperoleh melalui dari dalam  (endogen) maupun dari luar tubuh (eksogen). Pada keadaan patologis akibat paparan asap rokok menimbulkan ketidakseimbangan antara jumlah radikal bebas yang dihasilkan dalam tubuh sehingga dapat mengakibatkan terjadinya stress oksidatif.Kesimpulan:Peningkatan jumlah radikal bebas secara langsung akan berpengaruh pada mediator inflamasi pada tubuh. Peningkatan radikal bebas akan memicu proses inflamasi secara lokal pada saluran napas dan sistemik sehingga meningkatkan angka kejadian eksaserbasi pada penderita PPOK.